A Case Control Study To Determine The Association Of Blood Groups And Allergic Rhinitis - Chai, Hui Yi (2022)
The primary objective is to discover the association between ABO/rhesus blood groups and allergic rhinitis. Also, this study aimed to find out the association of demographic factors (gender and races) of patients and ABO blood groups.